Acehnese Local Wisdom Through the Lens of Acehnese Novelists During the Times of Political Conflict and Peace Agreement - Wildan Wildan; Yunisrina Qismullah Yusuf; Budi Arianto; Rajab Bahry (OKARA: Jurnal Bahasa dan Sastra, 2023)
Acehnese novelists have a role in expressing and preserving the socio-cultural conditions of the Acehnese people in Aceh, Indonesia, especially regarding the points of local wisdom in their works. This study deals with local wisdom as reflected in the novels by Acehnese novelists from 2005 to 2011, the times in which the Acehnese people endured the political conflict and peace agreement with the Indonesian government. It covers the aspects of forms and use of local wisdom embedded within the novels as narrated by the Acehnese authors in these rough times. It employed the qualitative-analytical method and content analysis technique. A number of nine selected novels written by Acehnese novelists and published between the years 2005-2011 were chosen for data analysis. The results showed that the local wisdom in the novels was categorized into four themes: (1) belief in myths, (2) preservation of historical values, (3) safeguarding traditional houses, and (4) the practice of greetings and nobility. This study has revealed the local wisdom believed and practiced by the Acehnese society through the novels. They take part in shaping the direction of society's life. These pearls of wisdom cover all sides of life to support a strong and bonded society.